Keunikan Pernikahan dalam Perspektif Hukum Adat Mandailing - Maisyaroh Maisyaroh; Nur Aida; Widya Sari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The pre-wedding procession in Mandailing tradition is a tradition that is still carried out today. Mandailing customary law regulates forms of marriage that reflect the community's kinship, cultural and religious values. Traditional weddings involve Dalihan Na Tolu—mora, kahanggi, and anak boru—as the core of the traditional procession. The wedding ceremony begins with a traditional meeting called makkobar or markkatai, where unique and formal greetings are used. Post-wedding processions such as marulahari, mangupa-upa and so on, all of this cannot be separated from the customs that are still inherent in Mandailing customs. All Mandailing traditional practices cannot be separated from the role of dalihan na tolu, especially in matters of marriage. This research uses a literature study method by analyzing traditional documents and related literature. The results show that Mandailing customs not only reflect cultural identity, but also strengthen social harmony and are able to adapt to changing times.